Genome-Wide Identification and Expression Analysis of Auxin-Responsive GH3 Gene Family in Pepper (Capsicum annuum L.) - Qiao-Lu Zang; Meng Wang; Lu Liu; Xiao-Mei Zheng; Yan Cheng (Plants)
As an auxin-responsive gene, Gretchen Hagen 3 (GH3) maintains hormonal homeostasis by conjugating excess auxin with amino acids in plant stress-related signaling pathways. GH3 genes have been characterized in many plant species, but the characteristics of pepper (Capsicum annuum L.) GH3 (CaGH3) gene family members in response to multiple stimulants are largely unknown. In this study, we systematically identified the CaGH3 gene family at the genome level and identified eight members on four chromosomes in pepper. CaGH3s were divided into two groups (I and III) and shared conserved motifs, domains, and gene structures. Moreover, CaGH3s had close evolutionary relationships with tomato (Solanum lycopersicum L.), and the promoters of most CaGH3 genes contained hormone and abiotic stress response elements. A protein interaction prediction analysis demonstrated that the CaGH3-3/3-6/3-7/3-8 proteins were possibly core members of the CaGH3 family interaction. In addition, qRT-PCR results showed that CaGH3 genes were differentially expressed in pepper tissues and could be induced by phytohormones (IAA, ABA, and MeJA) and abiotic stresses (salt, low temperature, and drought) with different patterns. In addition, CaGH3-5 and CaGH3-7 were cloned, and the sequences showed a high degree of conservation. Moreover, the results of subcellular localization indicated that they were located in the membrane and chloroplast. Notably, after overexpressing CaGH3-7 in tomato, RNA-seq was performed on wild-type and transgenic lines, and the differentially expressed genes were mainly enriched in response to external stimuli. This study not only lays the foundation for a comprehensive understanding of the function of the CaGH3 gene family during plant growth and stress responses but also provides potential genetic resources for pepper resistance breeding.